2006
DOI: 10.1590/s0034-70942006000100003
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre bupivacaína racêmica a 0,25% e bupivacaína com excesso enantiomérico de 50% (S75-R25) a 0,25%, associadas ao fentanil para analgesia de parto com deambulação da parturiente

Abstract: Both racemic and S75-R25 0.25% bupivacaine associated to fentanyl were effective for labor analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Spinal anesthesia performed with fine gauge disposable needles and administration of bupivacaine combined with adjuvant drugs into the subarachnoid space, is reported as effective technique in most caesarean sections [20][21][22]. Previous studies have indicated that administration of epidural bupivacaine in labor analgesia is an advantage because it is coupled with lower intensity of motor blockade [23,24] besides preserving the differential blockade of racemic bupivacaine [25][26][27][28]. The aim of this perspective, double blind randomized study was to evaluate and compare the effectiveness of bupivacaine-fentanyl, bupivacaineclonidine and bupivacaine-dexmetomodine on the quality of blockade and maternal and neonatal repercussions.…”
mentioning
confidence: 99%
“…Spinal anesthesia performed with fine gauge disposable needles and administration of bupivacaine combined with adjuvant drugs into the subarachnoid space, is reported as effective technique in most caesarean sections [20][21][22]. Previous studies have indicated that administration of epidural bupivacaine in labor analgesia is an advantage because it is coupled with lower intensity of motor blockade [23,24] besides preserving the differential blockade of racemic bupivacaine [25][26][27][28]. The aim of this perspective, double blind randomized study was to evaluate and compare the effectiveness of bupivacaine-fentanyl, bupivacaineclonidine and bupivacaine-dexmetomodine on the quality of blockade and maternal and neonatal repercussions.…”
mentioning
confidence: 99%
“…Those authors observed that pain intensity during the evolution of labor was similar between groups, except at 45 minutes, when patients on 0.25% bupivacaine (S75-R25) presented lower pain scores 11 .…”
Section: Discussionmentioning
confidence: 92%
“…The literature has demonstrated that the administration of epidural bupivacaine (S75-R25) is associated with lower intensity of motor blockade 8,9 , besides preserving the differential blockade of racemic bupivacaine, representing an advantage of its use in labor analgesia 10,11,12,13 . Parturientss who participated in this study received 0.25% bupivacaine (S75-R25) and 0.20% ropivacaine.…”
Section: Discussionmentioning
confidence: 99%